Effect of Boric and Oxalic Acid on Nucleation Mechanism, Composition, Morphology and Structure of Electrodeposited Ni Films - Hamdi, Fatima Zohra Karima; Rahmani, A.; Hamdi, A. (East European Journal of Physics, 2025)
Nickel thin films were electrodeposited onto copper substrates at room temperature using an aqueous electrolyte containing nickel sulfate, nickel chloride, and sodium sulfate. The effects of two additives (boric acid and oxalic acid) on the nucleation mechanism, crystallographic structure, surface morphology, and chemical composition of the resulting Ni films were systematically investigated using cyclic voltammetry (CV), chronoamperometry (CA), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). CV analysis revealed that the presence of additives shifted the cathodic peak potentials toward more negative values, suggesting an inhibition effect on nickel reduction. Chronoamperometric studies confirmed that Ni deposition followed a three-dimensional instantaneous nucleation mode, unaffected by the additives. XRD patterns showed that all Ni films had a face-centered cubic (FCC) structure with strong (111) orientation, while SEM images indicated denser and more homogeneous surface morphology in the presence of additives. EDS analysis confirmed the presence of Ni in all samples.